Wheat water productivity under saline irrigation in Northern China: a meta-analysis of effects and management practices - Jiang, Xiaohe; Cao, Heli; Wang, Ruopu; Li, Xinlong; Du, Taisheng; Tong, Ling; Kang, Jian; Gao, Jia; Ding, Risheng (Frontiers in Plant Science, 2026)
IntroductionSaline irrigation is an effective way to alleviate water scarcity in agriculture, but its productivity is constrained by salt stress. The effects of salinity on wheat yield and water productivity (WP), and how management practices can mitigate these effects, remain inadequately quantified.MethodsThrough a meta-analysis of 2265 observations from field studies in Northern China, we quantified the responses of wheat yield, WP, and associated traits to saline irrigation and evaluated the efficacy of key management practices.ResultsThe wheat yield (-16.3%) and WP (-13.7%) were significantly reduced under saline irrigation. Salt stress primarily inhibited photosynthetic rate (Pn), which subsequently reduced leaf area index (LAI) and plant height (PH), ultimately restricting spike number (SN) and yield, while constraining WP. A salinity threshold of 5 g/L was identified, beyond which the declines in yield and WP became severe. Alternate saline and freshwater irrigation ameliorated stress, increasing PH (+12.1%), SN (+7.4%), yield (+5.9%), and WP (+13.1%). Similarly, straw returning increased SN (+11.3%), yield (+12.3%), and WP (+12.5%).DiscussionThis study clarified the physiological cascade from salt stress to yield loss and confirm the critical role of the 5 g/L salinity threshold in sustaining wheat productivity. Alternate irrigation and straw returning mitigate salt stress through complementary pathways, enhancing plant growth and yield components. This meta-analysis provides evidence-based insights for optimizing saline irrigation management, supporting sustainable wheat production in water-scarce, salt-affected regions of northern China.